2014
DOI: 10.1248/bpb.b13-00880
|View full text |Cite
|
Sign up to set email alerts
|

Korean Red Ginseng Extract Exhibits Neuroprotective Effects through Inhibition of Apoptotic Cell Death

Abstract: Red ginseng has long been used as a traditional medicine in many East Asian countries including Korea. It is known to exhibit various pharmacological effects, including anti-oxidant, anti-cancer, anti-stress and anti-diabetes activities. To further explore its actions, the present study evaluated effects of Korean red ginseng (KRG) extract on neuronal injury induced by various types of insults using primary cultured rat cortical cells. KRG extract inhibited neuronal damage and generation of intracellular react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 37 publications
(113 reference statements)
2
39
0
Order By: Relevance
“…28) Briefly, the cells were washed with HCSS and exposed to 10 µM DCFH-DA in MEM for 30 min. Following this treatment, the cells were washed with HCSS and exposed to either 100 µM H 2 O 2 or X (0.5 mM)/XO (10 mU/mL) for 2 h in MEM in the absence or presence of various concentrations of luteolin.…”
Section: Measurement Of Intracellular Ros Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…28) Briefly, the cells were washed with HCSS and exposed to 10 µM DCFH-DA in MEM for 30 min. Following this treatment, the cells were washed with HCSS and exposed to either 100 µM H 2 O 2 or X (0.5 mM)/XO (10 mU/mL) for 2 h in MEM in the absence or presence of various concentrations of luteolin.…”
Section: Measurement Of Intracellular Ros Generationmentioning
confidence: 99%
“…For instance, luteolin was shown to exhibit neuroprotection against kainic acid-induced damage in rats and to improve learning and memory. 21) Using cultured cortical neuronal cells, it was reported that luteolin prevented amyloid β (A β ) (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) -induced neuronal cell death. 22) In a similar type of cultured cells treated with oxidative insult, luteolin was also found to markedly attenuate cytotoxicity and improve mitochondrial function as well as increase endogenous glutathione level and catalase activity.…”
mentioning
confidence: 99%
“…Red ginseng water extract (0.3–3 mg/mL) blocked ROS generation and neuronal apoptosis, which was stimulated by glutamate, N -methyl- D -aspartate, or β-amyloid in rat cortical cells. These results implied the potential of red ginseng to aid in the prevention of neuronal diseases [29]. Additionally, red ginseng extract (0.01–1 mg/mL; major constituents: Rb1, Rb2, Rc, Rd, Re, Rf, Rg1, and Rg3) was reported to have a neuroprotective effect on primary rat hippocampal neurons, where toxicity was induced by kainite, a glutamate analogue [30].…”
Section: Assessment Of Antioxidant Activities Of Red Ginseng In Cellsmentioning
confidence: 89%
“…Ginsenoside Rg2 reduced glutamate-induced cell death significantly through mechanisms related to anti-apoptosis and anti-oxidation in PC12 cells (Li et al 2007). A few studies also reported that the water extract of KRG protected cultured cortical cells from amyloid-β-induced apoptosis (Kim et al 2014) and repressed apoptosis in SK-N-SH cells by suppressing oxidative stress (Nguyen et al 2015). Therefore, the ginsenosides may play an important role in the observed prevention of apoptotic cell death in response to the KRG extract, but the possibility that other substances are involved in the anti-apoptotic effect still remains.…”
Section: Discussionmentioning
confidence: 99%